Laboratory measurements and calculations of line shape parameters of the H2O–CO2 collision system. (July 2019) - Régalia, L.; Cousin, E.; Gamache, R.R.; Vispoel, B.; Robert, S.; Thomas, X.
Highlights: New water vapor spectra broadened by CO2 recorded by FTS at room temperature in two spectral region: 2.7 and 6 µm. Retrieval of line parameters with multispectrum fitting procedure. Modified Complex Robert-Bonamy calculations. New measurements and calculations of H2 O broadened by CO2 line-shape parameters. Abstract: For decades, the remote sensing measurements have been made in planetary atmospheres in the Solar System and beyond. As the performance of the space instruments improves, the atmospheric science community is more and more in need of accurate spectroscopic data. The current databases offer some parameters for non-Earth atmospheres but are far from complete for all situations. For example, measured H2 O line parameters in CO2 -rich atmospheres such as Mars and Venus are missing while they are of prime importance to learn about the evolution of the atmospheres. New Fourier Transform Spectrometer spectra were recorded respectively around 2.7 and 6 µm, using a Connes' type FT spectrometer built in Reims. The spectra were analysed using a multispectrum fitting procedure to obtain the line-shape parameters of H2 O broadened by CO2 . Modified Complex Robert-Bonamy calculations of the half-width, line shift, and their temperature dependence were made in the spectral region from 1300 to 5000 cm −1 . The measurements and calculations are presented and compared with data available in the literature.